2020
DOI: 10.3390/cells9092005
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β and TNF-α Modulation of Proliferated and Committed Myoblasts: IL-6 and COX-2-Derived Prostaglandins as Key Actors in the Mechanisms Involved

Abstract: In this study, we investigated the effects and mechanisms of the pro-inflammatory cytokines IL-1β and TNF-α on the proliferation and commitment phases of myoblast differentiation. C2C12 mouse myoblast cells were cultured to reach a proliferated or committed status and were incubated with these cytokines for the evaluation of cell proliferation, cyclooxygenase 2 (COX-2) expression, release of prostaglandins (PGs) and myokines, and activation of myogenic regulatory factors (MRFs). We found that inhibition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 75 publications
1
35
0
Order By: Relevance
“…Inflammatory prostaglandin signaling plays a role in the preclinical development of neurodegenerative diseases [ 29 , 30 , 54 ]. COX-2, the inducible form of the COX enzyme involved in prostaglandin synthesis, is rarely expressed in steady state but is induced rapidly following stimulation by a mitogen, cytokine, or lipopolysaccharide [ 28 , 31 , 55 ]. Here, we found that COX-2 expression was increased following treatment of BV2 and HT22 cells with IL-22, and there was a time difference between the responses of the BV2 and HT22 cell lines at the transcriptional ( Figure 2 B) and translational levels ( Figure 2 C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory prostaglandin signaling plays a role in the preclinical development of neurodegenerative diseases [ 29 , 30 , 54 ]. COX-2, the inducible form of the COX enzyme involved in prostaglandin synthesis, is rarely expressed in steady state but is induced rapidly following stimulation by a mitogen, cytokine, or lipopolysaccharide [ 28 , 31 , 55 ]. Here, we found that COX-2 expression was increased following treatment of BV2 and HT22 cells with IL-22, and there was a time difference between the responses of the BV2 and HT22 cell lines at the transcriptional ( Figure 2 B) and translational levels ( Figure 2 C).…”
Section: Discussionmentioning
confidence: 99%
“…Activated microglia release various bioactive molecules, including nitric oxide and reactive oxygen species. In addition, cyclooxygenase-2 (COX-2) is an enzyme that produces prostaglandin E2 (PGE2), a major inducer of inflammatory processes in the hippocampus [ 28 , 29 , 30 , 31 ]. Hence, we examined the effects of IL-22 on IL-6, TNF-α, COX-2, and PGE2 expression in mouse brain cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…showed that inflammation induced by atrophy triggers the activation of COX-2 to promote proliferation via interleukin-1β and tumor necrosis factor-α 28 . We postulated that the activity of COX-2 might increase in the later phase of immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…TNFα ↓MyoD (Li and Reid, 2001;Alvarez et al, 2020) ↓Myoblast differentiation (Alvarez et al, 2020) ↓Myosin, actin, and sarcoplasmic proteins (Alvarez et al, 2020) ↑Protein catabolism (Cheema et al, 2000;Popa et al, 2007) ↑Glycolysis (Boscá and Corredor, 1984;Rhoades et al, 2005;Remels et al, 2015) ↓Glucose oxidation in β cells (Oleson et al, 2015) ↓Glucose-stimulated insulin secretion (Oleson et al, 2015) ↓Insulin sensitivity (Youd et al, 2000;Li and Reid, 2001) ↑Lipolysis in fat deposits (Cheema et al, 2000;Popa et al, 2007) IL-6 ↓Muscle hypertrophy (Haddad et al, 2005;Bodell et al, 2009) ↓Myoblast differentiation (Haddad et al, 2005;Posont et al, 2018) ↑Muscle atrophy (Haddad et al, 2005;Bodell et al, 2009) Altered islet structure (Campbell et al, 1994) ↑Fibrosis (Campbell et al, 1994) Impaired insulin signaling (Bruce and Dyck, 2004;Wolsk et al, 2010;Knudsen et al, 2017) ↓GH and IGF-1 secretion and sensitivity, multiple tissues (Haddad et al, 2005;Bodell et al, 2009) IL-1β ↑Protein catabolism (Nawabi et al, 1990;Dinarello, 2000;Li et al, 2009) ↓Myofiber width (Li et al, 2009) ↓Actin content (Li et al, 2009) ↑β cell apoptosis (Harms et al, 2015;Oleson et al, 2015) ↓Glucose-stimulated insulin sec...…”
Section: Skeletal Muscle Pancreatic Islets Othermentioning
confidence: 99%